Comparison of the three SARMs RAD-140, GLPG0492 and GSK-2881078 in two different in vitro bioassays, and in an in silico androgen receptor binding assay. Issue 189 (May 2019) - Zierau, Oliver; Kolodziejczyk, Annika; Vollmer, Günter; Machalz, David; Wolber, Gerhard; Thieme, Detlef; Keiler, Annekathrin Martina
Highlights: RAD-140, GSK-2881078 & GLPG0492 induced reporter gene expression in PC3(AR)2 cells. All three SARMs were androgenic in the yeast screen. Binding to the AR ligand-binding domain was investigated by molecular modeling. Abstract: Selective androgen receptor modulators comprise compounds that bind as ligands to the androgen receptor and possess tissue-selective activities. Ideally, they show agonistic properties in anabolic target tissues, while inducing antagonistic or only weak agonistic effects in reproductive organs. Due to their myoanabolic effects, selective androgen receptor modulators are included in the list of prohibited substances and methods of the World Anti-Doping Agency. In the current investigation, the androgenic potential of RAD-140, GSK-2881078 and GLPG0492 was comparably investigated in two different in vitro bioassays. In the yeast androgen screen, the androgenic effects were lower than in the reporter gene assay in prostate carcinoma cells ( e.g. for GSK-2881078, the EC50 values were 4.44 × 10 −6 M in the yeast screen and 3.99 × 10 -9 M in the prostate cells respectively). For future investigations, it is of importance whether the yeast androgen screen, which has been proven to detect androgenic compounds in urine, can detect an abuse of the selective androgen receptor modulators. Molecular modeling of the binding to the androgen receptor ligand binding domain suggests slight differences in the binding modes of RAD-140, GSK-2881078 and GLPG0492. In conclusion, androgenic activity of the three non-steroidal compounds in the two different in vitro test systems confirmed the results of the in silico modeling of the androgen receptor binding.